Risk stratification in patients with chronic stable angina pectoris - Śpiewak, Mateusz; Główczyńska, Renata; Starczewska, Marta E.; Pietrasik, Arkadiusz; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2006)
Individual prognosis and risk of cardiovascular events in patients with stable angina can vary by up to 10-fold. The aim of risk stratification is to identify high-risk individuals in order to introduce aggressive therapy in this group of patients. An estimated annual mortality rate >2% is considered high risk. The risk assessment should be based on: clinical evaluation, response to stress testing, quantification of ventricular function and coronary anatomy, as assessed by arteriography. However, not every patient requires risk stratification by all four points. The methods of evaluation and the risk assessment hierarchy depend on pre-test probability of coronary disease and on the general condition of the patient. The most common method of risk stratification in primary prevention is based on the SCORE evaluation system.